Nurses’ Perception of Therapeutic Communication: A Metaphor Study - Esra Uslu; Türkan Peşkirci; Aysel Özsaban; Gülcan Kendirkıran (Genel Tıp Dergisi)

(untitled)
Background and Aim: Therapeutic communication, vital for patient centered care, is often challenging for nurses to define. Metaphors offer a valuable tool for understanding this crucial aspect. This study was conducted to explain nurses' perceptions of therapeutic communication through metaphors.Methods: This study was conducted with metaphor analysis technique based on phenomenological approach with 189 nurses as participants. Data collection occurred via an online survey in 2023, where participants completed the sentence, “Therapeutic communication is like ... because ...' The qualitative data were analyzed using Braun & Clarke’s six-step thematic analysis method.Results: The study identified three main themes and nine subthemes. (i)Traits: magical, complex, continuous, essential, (ii)Benefits: offering support, healing, guidance, improving (iii)Obstacles: lack of awareness. Conclusions: Nurses perceived therapeutic communication positively, yet obstacles indicate a need for greater awareness. These findings underscore the necessity of studies to enhance nurses' skills and attitudes in therapeutic communication.